Increased risk of non-hematological cancer in young patients with aortic stenosis: a retrospective cohort study. (14th October 2021) - Shiran, A; Bental, T; Shapira, Y; Schwartzenberg, S; Sagie, A; Vaturi, M; Adawi, S; Fuks, A; Aronheim, A; Saliba, W
Abstract: Background: We have previously reported an increased risk for non-hematological malignancies in young patients with moderate or severe aortic stenosis (AS) (1). These findings were the result of a post-hoc analysis from a large echocardiography database and needed verification. Purpose: To determine, using a different study population, whether young patients with AS are at increased risk for cancer. Methods: A large echocardiographic database was used to identify patients (age≥20 years) with moderate or severe AS (study group) and patients without aortic stenosis (comparative group). The new occurrence of non-hematological malignancies was determined after the index date (first echo with moderate or severe AS or first recorded echo in the control group). Results: The final study group included 7, 013 patients with AS and 98, 884 without AS. During a median follow-up of 6.9 years (3.0–11.1) there were 10, 705 new cases of non-hematological cancer. The crude incidence rate of cancer was higher in AS compared to non-AS patients (22.3 vs. 13.7 per 1, 000 patient-year, crude HR 1.58 (95% CI 1.46–1.71). After adjustment for relevant covariates, there was no difference between groups (HR 0.93, 95% CI 0.86–1.01). Only patients in the lowest age quartile (20–49.7 years), had an increased adjusted risk of cancer (HR 1.91, 95% CI 1.08–3.39). The HR for the risk of cancer in AS was inversely proportional to age (P<0.001 for the interaction between AS and age) (Figure 1). Conclusion: Young patients with moderate or severe AS are at increased risk for cancer. Cancer surveillance should be considered for young patients with AS. FUNDunding Acknowledgement: Type of funding sources: None.